Asking and Giving Response Strategy to Improve the Elementary School Sixth Graders’ English Speaking Ability - Faridah Eka Fatmala (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The main problem in learning English is the lack of confidence in speaking ability, which hinders one’s mastery of English. This study aims to reveal the efficacy of employing asking and giving response strategy using English songs in improving the speaking ability of sixth graders’ students. This research was conducted using the online classroom action research method with Google Meet as the medium, held in two cycles with two meetings in each cycle. The result of this examination indicates that the strategy of asking and giving response using English songs can improve the English-speaking ability of sixth graders’ students.